Adipose‐tissue regulatory T cells: Critical players in adipose‐immune crosstalk. Issue 11 (20th September 2017) - Becker, Maike; Levings, Megan K.; Daniel, Carolin
Abstract: Obesity and type‐2 diabetes (T2D) are associated with metabolic defects and inflammatory processes in fat depots. FoxP3 + regulatory T cells (Tregs) control immune tolerance, and have an important role in controlling tissue‐specific inflammation. In this mini‐review we will discuss current insights into how cross‐talk between T cells and adipose tissue shapes the inflammatory environment in obesity‐associated metabolic diseases, focusing on the role of CD4 + T cells and Tregs. We will also highlight potential opportunities for how the immunoregulatory properties of Tregs could be harnessed to control inflammation in obesity and T2D and emphasize the critical need for more research on humans to establish mechanisms that are conserved in both mice and humans. Abstract : A cross‐talk between CD4 + T cells and FoxP3 + Tregs with adipose tissue shapes the local inflammatory environment in obesity‐associated metabolic diseases. We discuss opportunities how the immunoregulatory properties of FoxP3 + Tregs could be harnessed in order to maintain tissue‐homeostasis in obesity and emphasize the need for more translational research on humans.